(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Benign lymphoepithelial Cyst (BLEC) is one of the rare benign pathology of parotid gland. These painless cysts grow slowly which may mimic haemangioma, Warthin’stumour and lymphoma. Now a days BLEC incidence has increased due to increasing numbers of AIDS patients but it is very much rare in non HIV infected patients. In case of non HIV positive it is embryonic in origin. So surgeons should have concern about HIV infection when patient presents with lymphoepithelial cyst. In our case, patient is HIV negative. Bangladesh J Otorhinolaryngology 2025; 31 (1) Page-47-51